Housing loan evaluation system using artificial neural network - Azmi Raif Nur, Abd Wahab (2011)
Nowadays, billions of Malaysians are engaged to at least one housing loan contract when they buy their own houses,and thousands are still applying.A lot of work has to be done by the loan companies (banks) in order to determine the affordability and possibilities of payment.The use of artificial intelligent integrated system is widely known nowadays as it helps to lessen human burden with its effectiveness in making analysis and prediction.Therefore, the Housing Loan Evaluation System is developed to suits the need of the loan companies (banks) in making analysis generally.This system takes a list of factors related to the loan as inputs.Then,it filters out and sorts them according to the importance level.After that,the artificial neural network is used to make an evaluation and from the result, the company can choose to approve or not to approve the loan application.